E-Cigarette Use and Future Cigarette Initiation Among Never Smokers and Relapse Among Former Smokers in the PATH Study. (September 2019) - McMillen, Robert; Klein, Jonathan D.; Wilson, Karen; Winickoff, Jonathan P.; Tanski, Susanne
Objectives: Any potential harm-reduction benefit of electronic cigarettes (e-cigarettes) could be offset by nonsmokers who initiate e-cigarette use and then smoke combustible cigarettes. We examined correlates of e-cigarette use at baseline with combustible cigarette smoking at 1-year follow-up among adult distant former combustible cigarette smokers (ie, quit smoking ≥5 years ago) and never smokers. Methods: The Population Assessment of Tobacco and Health Study, a nationally representative, longitudinal study, surveyed 26 446 US adults during 2 waves: 2013-2014 (baseline) and 2014-2015 (1-year follow-up). Participants completed an audio computer-assisted interview in English or Spanish. We compared combustible cigarette smoking at 1-year follow-up by e-cigarette use at baseline among distant former combustible cigarette smokers and never smokers. Results: Distant former combustible cigarette smokers who reported e-cigarette past 30-day use (9.3%) and ever use (6.7%) were significantly more likely than those who had never used e-cigarettes (1.3%) to have relapsed to current combustible cigarette smoking at follow-up ( P < .001). Never smokers who reported e-cigarette past 30-day use (25.6%) and ever use (13.9%) were significantly more likely than those who had never used e-cigarettes (2.1%) to have initiated combustible cigarette smoking ( P < .001). Adults who reported past 30-day e-cigarette use (7.0%) and ever e-cigarette use (1.7%) were more likely than those who had never used e-cigarettes (0.3%) to have transitioned from never smokers to current combustible cigarette smokers ( P < .001). E-cigarette use predicted combustible cigarette smoking in multivariable analyses controlling for covariates. Conclusions: Policies and counseling should consider the increased risk for nonsmokers of future combustible cigarette smoking use as a result of using e-cigarettes and any potential harm-reduction benefits e-cigarettes might bring to current combustible cigarette smokers.